Acute scrotum as a complication of Thiersch operation for rectal prolapse in a child - Al-Momani Hashem; Saleem Mohammad M (BMC Surgery, 2006)
Abstract Background We report a case of acute scrotal condition that presented in a four year old male child one year after being treated for an idiopathic rectal prolapse utilizing Thiersch wire. Case presentation The acute scrotum had resulted from spreading perianal infection due to erosion of the circlage wire. The condition was treated with antibiotics and removal of the wire. The child made an uneventful recovery. Conclusion This case highlights that patients with Thiersch wire should be followed until the wire is removed. Awareness of anal lesions as a cause of acute scrotal conditions, and history and physical examination are emphasized.